RELATIONSHIP OF VICARIOUS TRAUMATIZATION WITH FAMILY RELATIONS AND COPING STRATEGIES AMONG HEALTHCARE PROFESSIONALS - Mustafa, Nazia; Haleem, Fahad; Khan, Najm Us Saqib; Sardar, Tahir; Akhtar, Muhammad Naveed; Mumtaz, Javaria (Pakistan Armed Forces Medical Journal, 2020)
Objective: To study the relationship of vicarious traumatization with family relations and coping strategiesamong Health care professionals along with to find out the frequency of vicarious traumatization.Study Design: Cross sectional study.Place and Duration of Study: Various hospitals in Rawalpindi and Islamabad, from Jan2018 to Jun 2018.Methodology: A sample of 170 healthcare professionals (doctors=39, psychiatrists=27, psychologists=36, nurses=30 and others=38) (men=67, women=103) were taken from various hospitals in Rawalpindi and Islamabad. Data was collected by using the secondary traumatic stress scale, the index of family relations and the brief COPE scale.Results: Results revealed that all the instruments have good reliability and there was significant positivecorrelation (r=0.71) between various aspects of VT (intrusion, avoidance and arousal) and poor family relations.Further analysis reflected that Emotion focused coping was positively correlated (r=0.22) with poor familyrelations whereas problem focused coping was negatively correlated (r=-0.39) with poor family relations.Conclusion: So it is concluded that vicarious traumatization must be addressed and identified in health settingand coping skills training must be part of healthcare professionals’ education programs.